Antigen B from Echinococcus granulosus enters mammalian cells by endocytic pathways. - Edileuza Danieli da Silva; Martin Cancela; Karina Mariante Monteiro; Henrique Bunselmeyer Ferreira; Arnaldo Zaha (Public Library of Science (PLoS), 2018)
Cystic hydatid disease is a zoonosis caused by the larval stage (hydatid) of Echinococcus granulosus (Cestoda, Taeniidae). The hydatid develops in the viscera of intermediate host as a unilocular structure filled by the hydatid fluid, which contains parasitic excretory/secretory products. The lipoprotein Antigen B (AgB) is the major component of E. granulosus metacestode hydatid fluid. Functionally, AgB has been implicated in immunomodulation and lipid transport. However, the mechanisms underlying AgB functions are not completely known.In this study, we investigated AgB interactions with different mammalian cell types and the pathways involved in its internalization. AgB uptake was observed in four different cell lines, NIH-3T3, A549, J774 and RH. Inhibition of caveolae/raft-mediated endocytosis causes about 50 and 69% decrease in AgB internalization by RH and A549 cells, respectively. Interestingly, AgB colocalized with the raft endocytic marker, but also showed a partial colocalization with the clathrin endocytic marker. Finally, AgB colocalized with an endolysosomal tracker, providing evidence for a possible AgB destination after endocytosis.The results indicate that caveolae/raft-mediated endocytosis is the main route to AgB internalization, and that a clathrin-mediated entry may also occur at a lower frequency. A possible fate for AgB after endocytosis seems to be the endolysosomal system. Cellular internalization and further access to subcellular compartments could be a requirement for AgB functions as a lipid carrier and/or immunomodulatory molecule, contributing to create a more permissive microenvironment to metacestode development and survival.